Environmental health research needed to inform strategies, policies, and measures to manage the risks of anthropogenic climate change - Kristie L. Ebi (BMC, 2021)
Abstract Anthropogenic climate change is affecting population health and wellbeing worldwide. The two main policy options to prepare for and manage these risks are adaptation and mitigation; significantly increased investments in each are urgently needed. However, medical research councils worldwide have provided minuscule amounts of funding for environmental health research to provide timely and useful insights on effectively protecting vulnerable populations and regions, for building climate-resilient health systems, and for promoting health system-related greenhouse gas emission reductions in a changing climate.